Akermanitic clinker unlocks the potential of Mg-silicates for carbonation cured construction materials - Arne Peys; Natalia Pires Martins; Fernando Prado Araujo; Peter Nielsen (Frontiers in Materials)
The global CO2 storage potential of Mg-silicate minerals is renowned. The valorization of residues containing these minerals via ex situ carbonation therefore seems an obvious pathway, however, significant levels of CO2 uptake have only been obtained for a limited range of minerals (e.g., olivines), using extreme reaction conditions or strong chemicals. This paper shows that the carbonatability of Mg-silicate resources can be engineered using a clinkering process to produce akermanite (Ca2MgSi2O7 or C2MS2), by heating a raw meal of Mg-silicates with 25–45 wt% of CaCO3 to 1,200°C–1,350°C. Akermanitic clinkers with optimized raw meal obtained 40-70 wt% crystalline akermanite and 70-85 wt% total akermanite (including potential nanocrystalline akermanite from the XRD amorphous part). Carbonation of pressed cylinders at 10 bar, 60°C, 100% CO2 and >90% RH provided 60–80 MPa compressive strength and a CO2 uptake of about 100 kg/t, revealing the new akermanitic clinker as potential binder for construction materials.